A functionalist (Skopos) approach to Arabic–English subtitling of Saudi comedy: Managing humor, dialect features, and identity cues - Alshaikhi, Turky (Research Journal in Advanced Humanities, 2026)
Saudi comedy has become increasingly visible to global audiences through streaming platforms, where Arabic–English subtitling mediates not only propositional meaning but also humor, dialectal style, and socially loaded identity cues. Saudi comedic discourse often relies on culturally situated incongruities, slang and taboo play, rapid stance-shifts, and dialect-indexed personae whose social meanings are difficult to reconstruct within the spatial–temporal constraints of subtitles. This article develops a functionalist model, grounded in Skopos theory and Nord’s notion of loyalty, for evaluating and designing subtitle solutions in Saudi comedy. Rather than treating humor loss, dialect flattening, or cultural explicitation as isolated ‘errors’, the model frames them as outcomes of purpose-governed translational action negotiated in a translation brief. Integrating core audiovisual translation scholarship on subtitling constraints and norms, linguistic and pragmatic theories of humor, and sociolinguistic accounts of indexicality and identity, the article proposes (i) a skopos hierarchy tailored to streaming comedy, (ii) criteria for identifying ‘load-bearing’ cues (humor triggers, dialect markers, identity signals), and (iii) a strategy repertoire—calibrated explicitation, selective retention/transliteration, controlled substitution, constrained compensation, and register mapping for code-switching and mock formality. To demonstrate operationalization, the article provides worked Saudi Arabic examples (in Arabic script with transliteration and gloss) and paired English subtitle options aligned with alternative briefs. The contribution is a practice-facing yet theoretically rigorous framework for research design, training, and quality assessment of Arabic–English subtitling of Saudi comedy in the era of global streaming.